2018
DOI: 10.3389/fneur.2018.00979
|View full text |Cite
|
Sign up to set email alerts
|

Functional Head Impulse Testing Might Be Useful for Assessing Vestibular Compensation After Unilateral Vestibular Loss

Abstract: Background: Loss of the vestibulo-ocular reflex (VOR) affects visual acuity during head movements. Previous studies have shown that compensatory eye-saccades improve visual acuity and that the timing of the saccade is important. Most of the tests involved in testing VOR are made with passive head movement, that do not necessarily reflect the activities of daily living and thus not being proportionate to symptoms and distresses of the patients.Objective: To examine differences between active (self-generated) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
(32 reference statements)
3
30
0
1
Order By: Relevance
“…not). Prior studies have shown that the frequency and velocity of CS do change over time with VPT (13,14,(40)(41)(42). Together, these data suggest that the current standard of care prescribing gaze stability exercises for VPT (sinusoidal head rotation) may not be restoring slow phase (i.e., vestibular) eye velocity during passive head rotation, but instead lead to an altered CS velocity putatively to improve gaze stability.…”
Section: Discussionmentioning
confidence: 75%
“…not). Prior studies have shown that the frequency and velocity of CS do change over time with VPT (13,14,(40)(41)(42). Together, these data suggest that the current standard of care prescribing gaze stability exercises for VPT (sinusoidal head rotation) may not be restoring slow phase (i.e., vestibular) eye velocity during passive head rotation, but instead lead to an altered CS velocity putatively to improve gaze stability.…”
Section: Discussionmentioning
confidence: 75%
“…After VOR loss short latency compensatory saccades can improve visual acuity [79][80][81][82], so the VOR and saccades provide complimentary and differential roles in gaze by generating compensatory velocity and position changes respectively [7,53]. The neuro-physiology of saccade modification after loss of the VOR could be explained by saccade motor learning paradigms, in man [83,84] and monkey [85,86], by which saccade characteristics are modulated over time by visual error feedback loops through the super colliculus and cerebellum [87][88][89][90][91][92].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline information about age, gender, illnesses, and medication was self-reported. Vestibular function was assessed by a specialist in neuro-otology (author MM) with the headshake test, Dix-Hallpike test ( 28 ), and head impulse test ( 29 , 30 ). The Timed up and Go test (TUG), Timed up and Go test with a cognitive task (TUGcog), and Timed Up and Go test with a manual task (TUGman) ( 31 ) were used for measuring balance.…”
Section: Methodsmentioning
confidence: 99%
“…The test was repeated randomly to each side. The test was considered pathologic if the tested person was not able to keep their eyes focused on the target, but responded with a corrective or compensatory saccade ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%